Toot batoot ki nazmein - Sufi, Tabassum; Jawad, Ahmed Rasheed (Feroz sons Lahore, 1999)
Toot Ba Toot Ki Nazmein is a collection of short, rhyming poems for children. These poems are often simple and repetitive, making them easy for young children to learn and recite. They often feature playful language, vivid imagery, and catchy rhythms.